Chemerin, Resistin, and Various Biochemical Markers in the Serum of Individuals Affected by Myocardial Infarction - Ali Adnan; Khaled Shaalan Sahab; Saad Mahmoud Ziadan (ASJ - Academic Science Journal, 2025)
Myocardial infarction (MI) is a widespread disease that may lead to death. Atherosclerosis is one of the main causes of a heart attack. Due to the narrowing of the arteries, it leads to the aggregation of LDL. As a result of this aggregation, a clot is formed. This clot leads to a complete or partial blockage of these arteries, followed by the death of a section of the heart muscle. Then, ischemic heart disease occurs because the heart’s need for oxygen is greater than the amount it receives. The study aimed to discover the relationship between the MI and alteration of chemerin, resistin and some myocardial biomarkers by evaluating this biomarkers in MI patients and to compare them with those of controls. The parameters which evaluated in study were cardiac enzymes including lactate dehydrogenase (LDH), aspartate aminotransferase (AST), creatine kinase MB (CK-MB), troponin I (TnI) and lipid profile (cholesterol (TC), triglycerides (TG), high density lipoprotein (HDL-C), low density lipoprotein (LDL-C), and very low density lipoprotein (VLDL-C)) in addition to chemerin and resistin. This study was conducted in Baqubah Teaching Hospital / Diyala Governorate from Jan/2023 until May /2023, Included the collection of samples were collected from patients lying in the cardiac care unit (CCU) who had suffered from myocardial infarction (MI). The study included 60 patients with an average age of (59.31±1.64) years, and the patients were compared with 60 healthy people as a control group, with an average age of (54.86±0.88) years. The result showed an increase in the levels of chemerin, resistin, TnI, LDH, AST and CK-MB significantly in patients of MI after 24-72hrs of entering attack. The ievels of lipid profile parameters were not changed significantly in patients of MI after admitted to Cardiac Care Unit (CCU) and this may due to receive of Hyperlipidemia drug. A correlation in a significant positive manner between resistin with chemerin, TG, VLDL-C, and CK-MB was observed, while HDL-C showed significant negative correlation with resistin in the patients group. Chemerin also has a significant positive correlation with TC in. No conclusion in the abstract the Levels of chemerin and resistin were observed to be significantly higher in patients compared to healthy controls, but the increase in chemerin and resistin was associated with changes in other parameters studied in patients. Therefore, the significant increase in chemerin and resistin may be used as new factors in monitoring or to indicate the extent of MI patients.